2013
DOI: 10.1097/ajp.0b013e3182478826
|View full text |Cite
|
Sign up to set email alerts
|

Acid Sensitization of Esophageal Mucosal Afferents

Abstract: (1) Esophageal acid infusion sensitizes it to subsequent electrical and chemical stimulation. (2) The acid-related sensitization is greater in gastroesophageal reflux disease than in controls and may influence in part symptom perception in this population. (3) Acid-related sensitization within the gastroesophageal reflux disease population is not dependant on mucosal inflammation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…GerdQ scores can assess the subjective symptomatic degree of GERD [ 12 ]. However, the severity of subjective symptoms in GERD is not only caused by acidity exposure, but also has a close correlation with visceral high sensitivity [ 15 ]. Our results only showed that the length of the PPGAP in the GERD patients had a significantly positive correlation with the GerdQ score.…”
Section: Discussionmentioning
confidence: 99%
“…GerdQ scores can assess the subjective symptomatic degree of GERD [ 12 ]. However, the severity of subjective symptoms in GERD is not only caused by acidity exposure, but also has a close correlation with visceral high sensitivity [ 15 ]. Our results only showed that the length of the PPGAP in the GERD patients had a significantly positive correlation with the GerdQ score.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, further investigation using GERD patients is needed to clarify the relationship between pH changes in different sites of the esophagus and generation of GERD symptoms during acid infusion, though a difference in sensitivity to acid between the upper and lower esophagus is also considered to be present in those patients 1-5. It was previously reported that an esophageal acid infusion induced stronger reflux symptoms in GERD patients compared to healthy controls 12. Indeed, the symptoms observed in our study were not strong.…”
Section: Discussionmentioning
confidence: 99%
“…It can be perceived as heartburn and regurgitation [33]. Sensitization of the esophageal mucosa by acid was described and these mechanistic studies offered an explanation for esophageal hypersensitivity to other stimuli such as balloon distention in patients with GERD [38]. Obesity was described as an important independent risk factor for GERD [39].…”
Section: Changes In the Diagnosis And Treatment Of Gerd And Nerd Over...mentioning
confidence: 99%